UGT1A1 genotype and irinotecan therapy: general review and implementation in routine practice. (4th May 2015) - Etienne‐Grimaldi, Marie‐Christine; Boyer, Jean‐Christophe; Thomas, Fabienne; Quaranta, Sylvie; Picard, Nicolas; Loriot, Marie‐Anne; Narjoz, Céline; Poncet, Delphine; Gagnieu, Marie‐Claude; Ged, Cécile; Broly, Franck; Le Morvan, Valérie; et al.
Abstract Irinotecan is a major drug in the treatment of advanced colorectal cancer. Its active form is the SN38 metabolite, which is cleared by the biliary route after glucuronidation by uridine diphosphate–glucuronosyltransferase 1A1 (UGT1A1). UGT1A1 activity exhibits a wide intersubject variability, in part related to UGT1A1 gene polymorphisms. The present review on the impact of the deficient UGT1A1*28 variant on irinotecan efficacy and toxicity was produced by a French joint workgroup comprising the Group of Clinical Onco‐pharmacology (GPCO‐Unicancer) and the National Pharmacogenetics Network (RNPGx). It clearly emerges that for irinotecan doses at least equal to 180 mg/m2, patients homozygous for the UGT1A1*28 allele are at increased risk of developing hematological and/or digestive toxicities. Irinotecan dose reduction is thus recommended in homozygous *28/*28 patients. In addition, this personalized medicine strategy aims to secure high‐dose irinotecan administration (≥240 mg/m2) that have proven to be safe in homozygous *1/*1 patients only. The clinical relevance of this test is discussed in terms of treatment efficacy improvement, as increasing the irinotecan dose appears to be safe in patients not bearing a deficient allele. Best execution practices, cost‐effectiveness, and result interpretation are discussed with the aim of facilitating the implementation of this analysis in clinical practice. The existence of networks of laboratories performing this test in routine hospital treatment, as in France, offers the prospect of widespread screening, thus guaranteeing equal access to safe treatment and optimized therapy for patients receiving irinotecan‐based therapy in advanced colorectal cancer.